2022
DOI: 10.1002/rev3.3363
|View full text |Cite
|
Sign up to set email alerts
|

International internships and skill development: A systematic review

Abstract: An increasing number of students complete an internship during their higher education studies in a country different from that of their home institution. A main advantage of this type of mobility is that it responds to employers' need for graduates with both hands‐on experience and global skills. In this paper, we attempt to review existing research on the types of skills higher education students gain through their participation in international internships. While there are several systematic reviews on study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Internships abroad offer students invaluable cultural immersion and skill development opportunities, preparing them for future job challenges. These experiences enhance professional competencies and global understanding (Pietro, 2022). Workplace learning, crucial for skill acquisition (Lierop et al, 2022), Integrating workplace learning with academics' bridges theory and practice, enhancing employability (Ruthanam, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Internships abroad offer students invaluable cultural immersion and skill development opportunities, preparing them for future job challenges. These experiences enhance professional competencies and global understanding (Pietro, 2022). Workplace learning, crucial for skill acquisition (Lierop et al, 2022), Integrating workplace learning with academics' bridges theory and practice, enhancing employability (Ruthanam, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the effectiveness of internships in different disciplines, such as tourism, hospitality, education, and medicine, has been a subject of interest. Studies have demonstrated that internships contribute to self-development, skill acquisition, and career readiness among students in diverse fields (Pietro, 2022;Patil & Sharma, 2022). These experiences not only provide students with hands-on learning opportunities but also shape their professional identities and prepare them for future roles in their respective industries.…”
Section: Opportunities Arising From Participation In International On...mentioning
confidence: 99%
“…Moreover, current research on skills acquired during internships can be divided in three skill domains namely cognitive domain, intra- and interpersonal domain (Pietro Di, 2022). The development of these skills in these domains have been reported to bring similar results as we have found in our professional and personal skill set, such as communication, cooperation and planning skills (Pietro Di, 2022). The additional value from co-creation in LLs is the academic skill set gained by students.…”
Section: Discussionmentioning
confidence: 99%
“…Research about traditional internships mainly focuses on the outcome for students in relation to professional development (Beck and Halim, 2008) and what the implications are for their employability (Gault et al, 2000(Gault et al, , 2010Silva et al, 2016). Moreover, current research on skills acquired during internships can be divided in three skill domains namely cognitive domain, intra-and interpersonal domain (Pietro Di, 2022). The development of these skills in these domains have been reported to bring similar results as we have found in our professional and personal skill set, such as communication, cooperation and planning skills (Pietro Di, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation